2020
DOI: 10.14254/2071-789x.2020/13-3/17
|View full text |Cite
|
Sign up to set email alerts
|

Employability in the fourth industrial revolution

Abstract: It is expected that the fourth industrial revolution will have a massive impact on individual career future experience by changing the basis of work, employment, and business in the upcoming future. Moreover, one-third of today's jobs will disappear by 2025 due to technology's intelligence development. Thus, students' employability skills are considered an effective tool to sustain employment at the future labour market. However, there are discrepancies in employability skills vision between higher education s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
(38 reference statements)
1
18
0
Order By: Relevance
“…The findings of the study showed that students lack the understanding of the sets of the employability skills of the fourth industrial revolution indicating a gap of employability skills provided by the HEIs and the labour market demands. The study recommended that the HE subject matter experts to review the programmes of the HEIs and enhance the programmes' learning outcomes to deliver the required future employability skills such as communication, IT skills, foreign languages, and team-work to prepare the students to compete in the future job market (Pauceanu, Rabie, & Moustafa, 2020).…”
Section: Literature Review Graduate Readiness For Employability Definitionsmentioning
confidence: 99%
“…The findings of the study showed that students lack the understanding of the sets of the employability skills of the fourth industrial revolution indicating a gap of employability skills provided by the HEIs and the labour market demands. The study recommended that the HE subject matter experts to review the programmes of the HEIs and enhance the programmes' learning outcomes to deliver the required future employability skills such as communication, IT skills, foreign languages, and team-work to prepare the students to compete in the future job market (Pauceanu, Rabie, & Moustafa, 2020).…”
Section: Literature Review Graduate Readiness For Employability Definitionsmentioning
confidence: 99%
“…However, it is also expected that the fourth industrial revolution will have a massive impact on careers and the job market by changing the basis of work, employment and business (Pauceanu et al, 2020). Moreover, it is also forecasted that due to significant development in artificial intelligence, one-third of today's jobs will disappear by 2025 (Brougham & Haar, 2017).…”
Section: Swot Analysis Of Industry 40 and The Impact On Learning Analyticsmentioning
confidence: 99%
“…Besides, the importance for Readiness for employability skills such as critical thinking, team-work, and communication skills necessary for success in the workplace of the 21st Century are effective when being taught in the curriculum of the HEIs (Evans, Davis, & Wheeler, 2017). In addition, special academic modules on development of Readiness for employability competencies combining both technical and soft skills can be included in the curriculum of the HEIs programmes to enhance graduates' employability (Manoharan & Arockiam, 2017;Pauceanu, Rabie, & Moustafa, 2020). Also, practical activities, combined with communication skills, and socio-emotional competencies were the most important requirement for labor market transition which highlights the importance of the integration of practical activities in engineering curriculum to prepare graduates for future employability (Edwin & Sabura, 2019;Monteiro et al, 2016).…”
Section: Hypothesis Testingmentioning
confidence: 99%